Pengaruh Kualitas SDM, Pemanfaatan Sistem Informasi Keuangan Daerah, dan Pengendalian Interen Akuntansi Terhadap Ketepatwaktuan Pelaporan Keuangan Pemerintah Daerah (Studi Empiris Pada Kabupaten dan Kotamadya di Provinsi Sumatera Barat) - Riza Agustia Sari; Fefri Indra Arza (Universitas Negeri Padang, 2016)
This study examines the effect of human resources quality, usefullness of local financial information system,and of accounting internal control on timeliness of local government financial reporting. Population of this research was accountingor financial staffon DPPKAD in West Sumatera province. The method of collecting the data was using questioner and analyzed with multiple regression.. The results showed that human resources quality, and accounting internal control have significant positive effect on timeliness of financial reporting, but usefullness of local financial information system does not affect on timeliness of financial reporting. This study suggested that local goverment should increase the human resources qualityand also optimizedusefullness of local financial information system. Keywords:Human resources quality, timeliness of financial reporting, usefullness of local financial information system and of accountancy intern controlling.